2019
DOI: 10.1111/iwj.13249
|View full text |Cite
|
Sign up to set email alerts
|

Local release of metalloproteinases and their inhibitors after a successful revascularisation procedure

Abstract: An altered balance between metalloproteinases (MMPs) and their inhibitor tissue inhibitor of metalloproteinases (TIMPs) may influence the healing process of a minor amputation following a successful vein graft. To speed up this process, negative pressure wound therapy (NPWT) and advanced moist wound dressing have

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Patients with diabetes and critical limb ischaemia (CLI) are chronic generally, and their history is often characterised by numerous hospitalisations for frequent complications such as infection, neuropathy (chronic severe pain), and foot ulceration 1 . Recently we showed the pivotal role of negative pressure wound therapy (NPWT) and different moisture dressings as advanced adjuvant therapy after adequate revascularisation 2 in patients with CLI 2‐5 ; moreover, several authors 6 showed that autologous platelet‐rich plasma (PRP) applied in patients with diabetes and CLI undergoing minor amputation can be effective to improve wound healing. In other important work, they also showed that PRP associated to skin graft procedures can be effective to speed up the healing rate of non‐healing ulcers 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with diabetes and critical limb ischaemia (CLI) are chronic generally, and their history is often characterised by numerous hospitalisations for frequent complications such as infection, neuropathy (chronic severe pain), and foot ulceration 1 . Recently we showed the pivotal role of negative pressure wound therapy (NPWT) and different moisture dressings as advanced adjuvant therapy after adequate revascularisation 2 in patients with CLI 2‐5 ; moreover, several authors 6 showed that autologous platelet‐rich plasma (PRP) applied in patients with diabetes and CLI undergoing minor amputation can be effective to improve wound healing. In other important work, they also showed that PRP associated to skin graft procedures can be effective to speed up the healing rate of non‐healing ulcers 7,8 .…”
Section: Introductionmentioning
confidence: 99%